Consumer preferences for the predictive genetic tests for Alzheimer’s disease - Huang, Ming-Yi; Perri III, Matthew (Farmeconomia. Health Economics and Therapeutic Pathways, 2012)
With the advent of predictive genetic tests, individuals will have the option to investigate their future risk of developing diseases like Alzheimer’s disease (AD). This knowledge can benefit people as they start to prepare themselves as well as their families for the disease process. The use of predictive genetic tests will likely increase as technology and genetic marker identification continues to advance. Thus, aligning the clinical practice of predictive genetic testing for Alzheimer’s disease with patient values and preferences has the potential to improve healthcare delivery. Several issues have been identified in this review regarding people’s preference when making a decision to test for AD, which include prediction value (i.e. false-positive/false-negative results), availability of treatments that would prevent or delay onset of AD, and anonymity/confidentiality. Literature indicates the most relevant issues regarding consumer preference for AD genetic testing is predictive value (accuracy). While fewer studies have discussed the effects of treatment availability or anonymity on consumer preference, these issues may become more important as technology continues to advance and public awareness of these issues increases. Future research in the area of consumer behavior with regard to predictive genetic testing is suggested.Most previous studies regarding consumer intent and preference for AD genetic tests have used small samples, convenience samples, or samples which were predominantly Caucasian, female and high socioeconomic status. Additionally, effects of most socio-demographics on the preference for AD genetic test are unclear in the literature. Conflicting results have been found regarding gender, education, income, and culture. An extension of the previous work using a larger and randomized sample may help to provide clearer relationship between these socio-demographics and consumer preference for AD genetic test.